2019
DOI: 10.1007/s12187-019-09631-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence School Climate on the Relationship between School Violence and Adolescent Subjective Well-Being

Abstract: School climate plays a key, protecting role against adverse outcomes when young individuals face peer victimization. Here we examined the potential relationships among adolescent's wellbeing, school violence, and school climate in a sample of 2006 Chilean students (48% female) aged 10-21 (M = 14.97, SD = 1.86) from 20 schools located in the same school department. Participants completed a self-report questionnaire assessing wellbeing, school violence, and school climate. Using multilevel (Hierarchical Linear M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 67 publications
2
28
0
13
Order By: Relevance
“…Finally, in previous studies school climate and life satisfaction were found to be negatively related to victimization (Martínez-Ferrer et al, 2011), and our results seem to confirm that the perceived school climate is an aspect of particular relevance of students life satisfaction (Suldo et al, 2013), including in situations in which someone is being bullied; the help and support of peers and teachers could prevent incidences of bullying, and as well as diminish the negative effect that bullying has on well-being (Flaspohler et al, 2009; Miranda et al, 2019; Rezapour et al, 2019; Varela et al, 2019; Zych et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Finally, in previous studies school climate and life satisfaction were found to be negatively related to victimization (Martínez-Ferrer et al, 2011), and our results seem to confirm that the perceived school climate is an aspect of particular relevance of students life satisfaction (Suldo et al, 2013), including in situations in which someone is being bullied; the help and support of peers and teachers could prevent incidences of bullying, and as well as diminish the negative effect that bullying has on well-being (Flaspohler et al, 2009; Miranda et al, 2019; Rezapour et al, 2019; Varela et al, 2019; Zych et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…We are aware, on the other hand, that subjective well-being can be affected by various situations experienced by adolescents, including school victimization (Savahl et al, 2018; Zych et al, 2018; Varela et al, 2019). Bullying is defined as “a phenomenon of intentional aggression by one or more persons upon another or others in a way that is both repeated and maintained over time, and in which a power imbalance exists between the aggressor and the victim” (Olweus, 1993, p. 9).…”
Section: Introductionmentioning
confidence: 99%
“…Excepciones a lo anterior son algunos estudios que evalúan el BS en la población nacional infantil y adolescente, incorporando otros aspectos de bienestar psicológico (acercándose con ello a la dimensión eudamónica), tales como relaciones interpersonales, estado de salud, bienestar económico, características del entorno, salud mental y autoestima (Dinisman & Ben-Arieh, 2016;Lawler, Newland, Giger, & Brockevelt, 2017;Oyarzún Gómez, Casas, Alfaro Inzunza, & Ascorra Costa, 2017;Varela et al, 2019).…”
Section: Las Limitaciones En La Investigación Del Bs En Chileunclassified
“…Conversely, literature shows that trusting in peers, establishing positive friendships at school, and receiving prosocial acts from schoolmates improve students' satisfaction with their lives and also with their schooling processes (Jiang et al, 2013;Huebner et al, 2014;Oyarzun et al, 2017;Su et al, 2019;Varela et al, 2019). These could be especially important for immigrant students' , for whom social relationships at school have also a great role in the promotion of their positive integration to the host country (Verkuyten and Thijs, 2002;Berry et al, 2006;Asendorpf and Motti-Stefanidi, 2017;Schachner et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%